A temporary farewell. Practices of Muslim women regarding mourning and remembrance. (2nd April 2020) - Ahaddour, Chaïma; Van den Branden, Stef; Broeckaert, Bert
ABSTRACT: The aim of this study is fourfold. First, we seek to elicit the practices of middle-aged and elderly Moroccan Muslim women regarding mourning and remembrance. Second, we aim to find out whether differences are observable between middle-aged and elderly women's practices. Third, we seek to explore the role of religion in these practices. Fourth, we aim to document how the actual practices of our participants relate to normative Islamic literature. Interviews were conducted with middle-aged and elderly Moroccan women living in Belgium ( n  = 30) and with experts in the field ( n  = 15). This study reveals that religious beliefs have a great impact on the practices of Muslim women. We found striking similarities between our participants' practices and normative Islamic literature.